The Maine Economy—Through a Different Lens - Knowles, William (Maine Policy Review, 2003)
William Knowles, a banker “from away” who has retired to Maine, gives his thoughts about the state’s economy, based on his reading, research, and conversations with a variety of Mainers. He structures his examination using four different “lenses,” which he terms: comparisons (how does Maine compare with other states and regions), cultivation (economic development), capital (especially human capital), and culture. Knowles challenges readers to think about whether Maine’s culture or belief system may be an important factor in restraining economic development.
Keywords: Maine economy